PEMANFAATAN JURNAL ELEKTRONIK SPRINGERLINK UNTUK MENDUKUNG PENELITIAN DI LINGKUNGAN LEMBAGA ILMU PENGETAHUAN INDONESIA - Tupan Tupan (Jurnal IPI (Ikatan Pustakawan Indonesia), 2018)
The study aims to find out the use of the springerlink electronic journal to support research in the Indonesian Institute of Sciences. The utilization of the Springerlink e-journal that was studied included the utilization based on the subject, year and work unit in the Indonesian Institute of Sciences. The study was conducted using survey methods by looking at the active LIPI community using the Springerlink database. The study was conducted for 3 years, from 2015-2017. The results showed that the use of electronic journals from the Springerlink database based on the most number of years was 2017 and followed in the 2nd position in 2016. The most usage occurred in August both in 207 and 2016. Based on the most subjects during 2015-2017 is Biomedical and life science, followed by the subject of Chemistry and Material Sciences and Earth and Environmental Science. While the usage based on the most work units is the Biology Research Center, then followed by the Bogor Botanical Garden Plant Conservation Center, the Geotechnology Research Center and the Chemical Research Center